GLP‐1 Is a Coronary Artery Vasodilator in Humans. Issue 22 (20th November 2018) - Clarke, Sophie J.; Giblett, Joel P.; Yang, Lucy L.; Hubsch, Annette; Zhao, Tian; Aetesam‐ur‐Rahman, Muhammad; West, Nick E. J.; O'Sullivan, Michael; Figg, Nichola; Bennett, Martin; Wewer Albrechtsen, Nicolai J.; Deacon, Carolyn F.; et al.
Abstract : Background: The mechanism underlying the beneficial cardiovascular effects of the incretin GLP‐1 (glucagon‐like peptide 1) and its analogues in humans is elusive. We hypothesized that activating receptors located on vascular smooth muscle cells to induce either peripheral or coronary vasodilatation mediates the cardiovascular effect of GLP‐1. Methods and Results: Ten stable patients with angina awaiting left anterior descending artery stenting underwent forearm blood flow measurement using forearm plethysmography and post–percutaneous coronary intervention coronary blood flow measurement using a pressure‐flow wire before and after peripheral GLP‐1 administration. Coronary sinus and artery bloods were sampled for GLP‐1 levels. A further 11 control patients received saline rather than GLP‐1 in the coronary blood flow protocol. GLP‐1 receptor (GLP‐1R) expression was assessed by immunohistochemistry using a specific GLP‐1R monoclonal antibody in human tissue to inform the physiological studies. There was no effect of GLP‐1 on absolute forearm blood flow or forearm blood flow ratio after GLP‐1, systemic hemodynamics were not affected, and no binding of GLP‐1R monoclonal antibody was detected in vascular tissue. GLP‐1 reduced resting coronary transit time (mean [SD], 0.87 [0.39] versus 0.63 [0.27] seconds; P =0.02) and basal microcirculatory resistance (mean [SD], 76.3 [37.9] versus 55.4 [30.4] mm Hg/s; P =0.02), whereas in controls, there was an increase in transit time (mean [SD], 0.48 [0.24] versus 0.83 [0.41] seconds; P <0.001) and basal microcirculatory resistance (mean [SD], 45.9 [34.7] versus 66.7 [37.2] mm Hg/s; P =0.02). GLP‐1R monoclonal antibody binding was confirmed in ventricular tissue but not in vascular tissue, and transmyocardial GLP‐1 extraction was observed. Conclusions: GLP‐1 causes coronary microvascular dilation and increased flow but does not influence peripheral tone. GLP‐1R immunohistochemistry suggests that GLP‐1 coronary vasodilatation is indirectly mediated by ventricular‐coronary cross talk.